Madrasah Management Improving Quality at MIS IT Nurul Ikhwan Cahaya Ananda Palembang (International Journal of Education and Literature, 2025)
Improving the quality of education is a strategic challenge for every educational unit, including private elementary madrasahs that carry the Integrated Islamic approach. MIS IT Nurul Ikhwan Cahaya Ananda Palembang as a basic educational institution based on Islamic values ​​and technology, faces various dynamics in managing quality management, ranging from limited resources to the complexity of implementing an internal quality assurance system. This study aims to describe in depth the management strategies applied in improving the quality of education, as well as identifying the challenges and solutions faced by madrasahs in the implementation process. The research method used is descriptive qualitative with data collection techniques in the form of observation, documentation, and in-depth interviews with key informants. The results of the study indicate that madrasahs have implemented quality management through strategic planning, strengthening teacher capacity, integrating technology in learning, and community involvement. Despite challenges such as budget limitations and imbalances in HR competencies, madrasahs are able to present solutions based on collaboration and innovation that are oriented towards the sustainability of education quality.